The Inflation Rate on Unemployment in Thailand - Rowiyah Asengbaramae (Proceeding of The International Conference on Economics and Business, 2022)
The purpose of this study is to evaluate the impact of changes in the inflation rate on the unemployment rate in Thailand over the period 2018-2022, with secondary data obtained from the World Bank as a source of information. The approach used in data analysis is through descriptive qualitative research methods and literature studies by referring to previous research journals relevant to the topic, as well as accessing data through websites as published sources of information. The results of this study indicate that during the period, there were fluctuations in the development of the inflation rate and the unemployment rate in Thailand. In general, there is a tendency that when the inflation rate decreases, the unemployment rate increases. This result is consistent with the theory proposed by A.W. Philips, where low unemployment rates are often associated with high inflation rates. In contrast, high unemployment rates are often associated with low inflation rates.